NOx Enriched Flue Gas Fixation for Biomass Production of Chlorella Vulgaris Buitenzorg - Dianursanti, Dianursanti; Nasikin, Mohammad; Wijanarko, Anondho (ASEAN Journal of Chemical Engineering, 2010)
Cultivation of Chlorella vulgaris Buitenzorg in a pilot scale of bubble column photo bioreactor using simulated NOx enriched flue gas concluded that presence of N2O as simulated NOx pollution (0.02%) in blowing bubbled air and CO2 is not so significant, compare to control experiment that was designed by absence of N2O (around 20% decreased). Meanwhile, presence of N2O tends a less significantly decreasing of μ - specific growth rate and qCO2 – specific CO2 transferred rate. It is around 30% decreased in both of μ and qCO2. Then, cultivation by presence of NOx in blowing simulated flue gas could drastically decreased intracellular carotene and lipid content and become increase to level near to both of pigment and lipid content in control experiment. Furthermore, cultivation by presence of NOx in blowing simulated flue gas also could drastically exchange intracellular fatty acid content and it become dominated by 16:0 species. Finally, refreshing cellular growth product with re-cultivation by blowing fresh air, could be restored the fatty acid content nearly to beginning microbial fatty acid content. It was happened cause of converting hexadecanoate species to octadecanoate species and it was shown that oleate (18:1) was dominating species.